Carnosol ameliorated cancer cachexia-associated myotube atrophy by targeting P5CS and its downstream pathways - Qiao-Yu Fang; Yue-Ping Wang; Rui-Qin Zhang; Meng Fan; Li-Xing Feng; Xiao-Dong Guo; Chun-Ru Cheng; Xiong-Wen Zhang; Xuan Liu (Frontiers in Pharmacology, 2024)
Introduction: Carnosol exhibited ameliorating effects on muscle atrophy of mice developed cancer cachexia in our previous research.Method: Here, the ameliorating effects of carnosol on the C2C12 myotube atrophy result from simulated cancer cachexia injury, the conditioned medium of the C26 tumor cells or the LLC tumor cells, were observed. To clarify the mechanisms of carnosol, the possible direct target proteins of carnosol were searched using DARTS (drug affinity responsive target stability) assay and then confirmed using CETSA (cellular thermal shift assay). Furthermore, proteomic analysis was used to search its possible indirect target proteins by comparing the protein expression profiles of C2C12 myotubes under treatment of C26 medium, with or without the presence of carnosol. The signal network between the direct and indirect target proteins of carnosol was then constructed.Results: Our results showed that, Delta-1-pyrroline-5-carboxylate synthase (P5CS) might be the direct target protein of carnosol in myotubes. The influence of carnosol on amino acid metabolism downstream of P5CS was confirmed. Carnosol could upregulate the expression of proteins related to glutathione metabolism, anti-oxidant system, and heat shock response. Knockdown of P5CS could also ameliorate myotube atrophy and further enhance the ameliorating effects of carnosol.Discussion: These results suggested that carnosol might ameliorate cancer cachexia-associated myotube atrophy by targeting P5CS and its downstream pathways.